CUMULATIVE INEQUALITY: A LENS TO UNDERSTAND STRUCTURAL DISCRIMINATION AND ITS EFFECT ON HEALTH. (11th November 2018) - Gonzales, E; Jung, L; Lee, Y; Wang, Y
Abstract: Utilizing cumulative inequality theory, this longitudinal population-based study aims to explore the association between cumulative experiences of discrimination and effects on health. Respondents aged 51+ were drawn from the Leave Behind Questionnaire from the Health and Retirement Study in 2006 and followed to 2014 (N=7, 100). Mixed effects models evaluated associations between discrimination (major lifetime discrimination, living in disadvantaged neighborhoods, perceived chronic workplace discrimination, everyday discrimination) and health (cognitive functioning, depression, self-rated health, loneliness, and life satisfaction). We created a "Summative Discrimination Scale (SDS)" that combines all ecological domains of discrimination (Cronbach's alpha .79). African Americans reported lower levels of health at baseline. Hispanics and African Americans experienced greater levels of depression and lower levels of cognition when compared to Whites. African Americans also reported higher levels of major discrimination, neighborhood physical disorder, and lower levels of social cohesion. African Americans also had slightly higher scores on the SDS, followed by Whites and then Hispanics. All forms of discrimination were related to depression and life satisfaction. Moderation tests support the double and triple jeopardy hypothesis, where racial and ethnic minorities, older adults, and women, had worse health outcomes when compared to their counterparts. To our knowledge, this is the first population-based study to employ cumulative disadvantage theory to explore the accumulation of discriminatory contexts and its effects on health. Preliminary analyses offers strong support of cumulative inequity hypotheses. Policy implications will be discussed.